KEWIRAUSAHAAN DIGITAL SEBAGAI STRATEGI TRANSFORMASI UMKM LAMPUNG - Aryan Danil Mirza. BR; Joni Putra; Agrianti Komalasari; Retno Yuni Nur Susilowati (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving regional economic growth, but still face challenges in the digital era, particularly in terms of digital literacy and financial management. This community service activity aims to increase the capacity of MSMEs in utilizing digital technology and strengthening financial literacy. The activity was held at Maharindu Kopi, Bandar Lampung, and was attended by 12 MSME actors from the food and beverage sector, makeup services, Pahawang tour services, and honey products. The implementation method was an interactive workshop covering three main topics, namely digital marketing and financial literacy (cost of goods sold and profit calculation). The results of the activity showed a significant increase in participants' understanding based on a comparison of pre-test and post-test scores. Overall, this activity had a positive impact on strengthening the competitiveness of MSMEs in the digital era, while also making a real contribution to building a digital entrepreneurship ecosystem in Lampung Province.